Proposta de atualização da área de Engenharia do produto na Universidade Federal do Pampa visando atender as novas diretrizes curriculares nacionais - (:unkn) unknown (Universidade Federal do Pampa, 2020)
In 2019, the new National Curriculum Guidelines for Engineering Bachelor Degree were approved and formalized through Resolution No. 2 of the "Câmara de Educação Superior do Conselho Nacional de Educação", aiming to update the Programs Pedagogical Models or "PPC" within a period of three years. Considering this, the Unipampa’s Industrial Engineering Program started the process of reformulating its "PPC". The demand imposed by the new guidelines and the ongoing reformulation process provided the panorama for this scientific work. One important area in an industrial engineer's academic formation is Product Engineering, which is the focus of the research to be developed. The aim was to propose the adequacy of the Product Engineering area of the Unipampa’s Industrial Engineering Program that includes the new national guidelines, the egress profile established in the program's PPC, the recommendations of the Academies and the "Conselho Federal de Engenharia e Agronomia – CONFEA", as well as the good practices adopted in the Industrial Engineering degrees of the Federal Universities with General Degree Index - "IGC 5". It also aimed to analyze aspects related to the regulations surrounding the Engineering, as well as the disciplines programs and credit hours of the Product Engineering area and syllabus that constitutes a basic source of inquiry. The methodology for the development of the research in this work was characterized in relation to nature as applied, as the objectives in exploratory, as the approach in qualitative and as the methods because of its bibliographic and documentary type. After applying the methodology, the main factors that meet the guidelines and compatibility with what is applied in the studied institutions were obtained, as well as the identification of weaknesses subject to improvement in the area.
Keywords: Diretrizes; Engenharia do Produto; Projeto pedagógico do curso; Industrial Engineering; Guidelines; Program Pedagogical Model; CNPQ::ENGENHARIAS